2001
DOI: 10.1097/00042560-200109010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With HIV Infection Among Young Gay and Bisexual Men in Canada

Abstract: Our data indicate that HIV-positive gay and bisexual men are more likely to be living in unstable conditions and to report more risky sexual and substance use behaviors than HIV-negative men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…3b). Two studies among MSM in BC and QC found HIV prevalence ranged from 3.5 to 6.4% for Aboriginal men compared with 1.4 to 3.5% for non-Aboriginal MSM [42,55]. However, a recent abstract by Liu et al reports a much higher HIV prevalence of 32.3% among Aboriginal men in ON, although rates reported for almost all ethnic/ racial groups in this study were high, with Aboriginal men the second highest group.…”
Section: Hiv Prevalencecontrasting
confidence: 72%
See 3 more Smart Citations
“…3b). Two studies among MSM in BC and QC found HIV prevalence ranged from 3.5 to 6.4% for Aboriginal men compared with 1.4 to 3.5% for non-Aboriginal MSM [42,55]. However, a recent abstract by Liu et al reports a much higher HIV prevalence of 32.3% among Aboriginal men in ON, although rates reported for almost all ethnic/ racial groups in this study were high, with Aboriginal men the second highest group.…”
Section: Hiv Prevalencecontrasting
confidence: 72%
“…The remaining included: three from ON [48][49][50]; two from AB [51,52]; one from MB [53]; one from SK [54]; one that used data collected from BC and QC [55]; one that used data collected from both QC and the NT [56]; one on BC and AB [57]; one from across Canada [58], and one with combined data from BC, AB, MB, ON, QC, NT, NS and NF [59]. The years studied ranged from 1980 to 2008 [46,58], with the majority using data since 1996.…”
Section: Setting Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with these findings, several countries have witnessed a resurgence in the incidence of HIV infection and other sexually transmitted diseases (STDs) among men who have sex with men (MSM) 4,5,6,7 , especially among young gay men 5,8 .…”
Section: Introductionmentioning
confidence: 99%